Effect of Short- and Long-term Use of Home and In-Office Bleaching with Carbamide Peroxide and Hydrogen Peroxide on Enamel Microhardness - Ameli, Nazila; Kianvash Rad, Niloofar; Nikpour, Farzane; Ghorbani, Raheb; Mohebi, Shadi (UI Scholars Hub, 2020)
Bleaching is a well-known esthetic dental treatment performed to lighten the tooth shade. Among different cosmetic dental procedures, including direct and indirect tooth-colored restorations, bleaching is likely the most conservative approach. Bleaching has been accepted well by patients and proven as a safe and effective approach. Objective: Tooth bleaching can be conducted at home or in offices. This study was performed to compare the enamel microhardness before bleaching and one and eight weeks after the application of different bleaching agents. Methods: Forty human premolars were randomly divided into four groups, and their buccal surface underwent a Vickers microhardness test before and after bleaching. Bleaching was performed with 40% hydrogen peroxide (HP) in-office bleaching agent (n = 10), 15% HP at-home bleaching agent (n = 10), and 15% carbamide peroxide (CP) at-home bleaching agent (n = 10) for two weeks. Ten samples were stored in artificial saliva and set as the control group. The microhardness of the samples was measured again one and eight weeks after bleaching. Results: The microhardness significantly decreased in the four groups one week after bleaching. Conclusion: The enamel microhardness was temporarily decreased by in-office bleaching. However, the microhardness increased with time and returned to the baseline value. Although the enamel microhardness initially reduced, it increased eight weeks after 15% CP at-home bleaching agent was applied.